A potência do comum desde o levante dos malês - Oliveira, Cinara Brito de (2022)
This study aimed to analyze the Malês Revolt, one of the main enslaved uprisings that occurred in Brazil, identifying whether the force of the common can be an effective instrument of reality transformation. It is a qualitative research and it uses documentary research as data collection process. Volume number 50 of the Annals of Public Archive of the State of Bahia, which assembles part of the judicial processes regarding the Revolt, was analyzed. Supported by the ethicalepistemological principles of Social-Historical Psychology and dialectical and historical materialism methodology, it sought in the subtext, according to Vigotski’s recommendation, the comprehension of thoughts, affections and meanings, which sustained the action of the Malês, in other words, its affectivevolitional base. The results show that the common was built within the Malê people through daily life meetings, by transgressing circulation and use of the territories in which they lived and or worked, as resistance strategy to the inhuman conditions to which they were submitted. The common presents as potentiality, individual and collective, in its ontological dimension, according to Spinosa’s assumptions of freedom search, providing the emergence of a political subject, a multitude, capable of confronting dominant power. Thus, the research shows the common can be an effective instrument of reality transformation